Environmental dimension of innovation: time series evidence from Turkey - ARI, ALİ (SPRINGER, 2020)
The study aims to investigate whether domestic innovation reduces environmental degradation in Turkey. Since the empirical literature on this subject is relatively poor and there is no empirical evidence for the Turkish case, the study attempts to bring a new perspective to the existing literature. To do this, the study estimates the relationship between innovation and CO2 emissions over the period of 1971-2013, via the ARDL bounds test and threshold cointegration test. Empirical results obtained from the ARDL approach indicates that the relationship between CO2 emission level and number of domestic patents depicts an inverted U-shape curve for Turkey. Moreover, estimation results show that urbanization, income level and financial development have positive effects on CO2 emissions, while alternative energy sources and human capital negatively affect the emission level. Since the linear econometric methods may yield inconsistent and biased results in the presence of a nonlinear relationship, the threshold cointegration method is employed as a robustness check. The findings obtained from threshold cointegration confirm the existence of a nonlinear relationship between CO2 emissions and domestic innovation. This suggests that for early stages of economic development, increases in domestic innovation raise the CO2 emission level in Turkey, but after achieving a certain development level, increases in domestic innovation lead to decreases in CO2 emissions. Thus, either developing or developed countries can eventually reduce CO2 emission levels by concentrating on innovation. Policy makers and institutions dealing with environmental issues should certainly pay attention to innovation and technological progress to assure a sustainable growth path.
Keywords: Innovation; Environmental degradation; CO2 emissions; ARDL bounds test; Threshold cointegration; VECTOR ERROR-CORRECTION; ECONOMIC-GROWTH; KUZNETS CURVE; CO2 EMISSIONS; ENERGY-CONSUMPTION; EMPIRICAL-EVIDENCE; THRESHOLD COINTEGRATION; FINANCIAL DEVELOPMENT; NUISANCE PARAMETER; STRUCTURAL-CHANGE